BEHIND THE BURDEN: A QUALITATIVE STUDY ON CAREGIVING FOR SUBSTANCE USE DISORDER IN PAKISTAN - Azad, Abrar Hussain; Gilani, Irum; Ali, Ijaz; Ghani, Usman; Malik, Laraib Fatima; Shabbir, Afifa; Umar, Shaaray Abrar; Wazir, Pashma (Journal of Ayub Medical College Abbottabad, 2024)
Background: Substance Use Disorder (SUD) poses severe challenges for both individuals with addiction and their caregivers. Caregivers in Pakistan experience psychological distress together with economic hardship and social discrimination which healthcare systems fail to recognize and address. Through this research both practical and emotional aspects of caregiving life of people who care for addicts (PWSUD) in Pakistan were studied. Methods: This qualitative study recruited 50 informal caregivers (male: 38, female: 12) through snowball sampling. The research team gathered information through advanced interviews that examined caregivers' experiences with caregiving roles while investigating treatment option awareness and obstacles to medical assistance. Research participants participated interviews conducted in Urdu followed by transcription and translation and data analysis through Braun and Clarke’s thematic analysis methodology. Results: Stigma and social rejection enhanced emotional distress among caregivers who experienced symptoms of anxiety depression and helplessness. Thematic analysis identified three primary themes: The research uncovered three main themes which encompass socio-economic challenges such as social isolation and lack of educational resources beside economic struggles together with survival skill deficits. Financial instability arose for caregivers because of continuous care responsibilities which restricted their access to professional treatments for their family members. Caregivers suffered from mental health problems because social stigma surrounding addiction both kept them isolated and prevented them from getting external support. Conclusion: The individuals who care for people with substance use disorders in Pakistan experience heavy emotional and social burdens together with financial stress while receiving almost no support. Accessible mental health services together with financial support programmes and stigma reduction interventions represent essential elements in supporting caregiver health and enhancing treatment results for individuals with Substance Use Disorder (PWSUD).